A numerical investigation of the influence of wind on convective heat transfer from the human body in a ventilated room. (15th January 2021) - Xu, Jingxian; Psikuta, Agnes; Li, Jun; Annaheim, Simon; Rossi, René M.
Abstract: As an important factor in indoor human thermal comfort, the wind is investigated in the present study using a fully validated human body-environment interface model based on CFD technology. The three parameters of air speed (va, 0.5–2 m/s), turbulence intensity (TI, 5%–40%) and wind direction (0°–180°) were simulated to study their influence on the convective heat transfer coefficient (hc ) at the surface of the human body. It was found that va influenced the value of hc more than TI. The influence of TI on hc reached a steady level when va was above 1.5 m/s; for example the greatest rate of change of hc at the head remained at 52% as the TI was increased from 5% to 40%. The wind direction had a noticeable influence on the overall hc when the va was above 0.5 m/s. A 90° wind (i.e. from the right side) gave a value of hc that was about 20% lower than wind from other directions, and led to an asymmetrical distribution of hc over the body surface. Locally, the wind direction did not influence hc at the head and feet, and influenced the central segments more than the limbs. Two regression equations for the correlations between hc and va, TI and wind direction were also generated and validated for continuous evaluation of hc . The resulting database of values for hc can be used in combination with the human thermoregulation models for thermal response prediction in built spaces with increased air speed. Highlights: The influence of turbulence intensity on convective heat transfer of human body remains steady for air speeds over 1.5 m/s. The wind direction influences the convective heat transfer coefficient of human body as the air speed exceeds 0.5 m/s. The wind from side causes an asymmetrical distribution of convective heat loss. Regression relationships between hc and air speed, turbulence intensity and wind direction are proposed.